Security and privacy in internet of things (IoTs) models, algorithms, and implementations - Hu, Fei (CRC Press, Taylor & Francis Group, 2016)
The Internet of Things (IoT) has attracted strong interest from both academia and industry. Unfortunately, it has also attracted the attention of hackers. How do we use efficient algorithms, models, and implementations to cover the four important aspects of IoT security, i.e., confidentiality, authentication, integrity, and availability?" The book consists of five parts covering attacks and threats, privacy preservation, trust and authentication, IoT data security, and social awareness.